Gestión del talento humano y su impacto en el desempeño laboral del personal administrativo del centro gerontológico de Quevedo, 2023. - Villon Ripalda, Lourdes Katherine (2025)
The objective of this research is to analyze human talent management and its impact on the job performance of the administrative staff at the Gerontological Center of Quevedo, year 2023. The study was conducted using a mixed-methods approach, with an exploratory, descriptive, and field research design. The inductive, deductive, and statistical methods were applied. The population considered for the study included the administrative and technical staff of the gerontological center, with the entire population of 34 collaborators taken as the sample due to its small size. Additionally, interviews were conducted with the Head of Human Talent and technical staff. The research results identified a direct relationship between human talent management and job performance: the combined analysis of interviews and surveys revealed that the Gerontological Center of Quevedo faces structural weaknesses that hinder optimal job performance. Although there are institutional efforts aimed at improvement, these are not always reflected in employee motivation or the quality of service provided to elderly users. Performance indicators show a high level of goal achievement and participation in training activities; however, feedback mechanisms and job satisfaction levels are low. Furthermore, Pearson’s correlation demonstrated a significant relationship between human talent management and job performance. These findings lead to the conclusion that the absence of strategic processes in talent management—such as competency-based recruitment, planned training, performance evaluation, and recognition policies—significantly limits its impact, evidencing a functional and reactive management style that deepens performance gaps among administrative staff.